2014
DOI: 10.1371/journal.pone.0115963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aging on the Regenerative Properties of Bone Marrow-, Muscle-, and Adipose-Derived Mesenchymal Stem/Stromal Cells

Abstract: Mesenchymal stem/stromal cells (MSCs) are promising cell sources for regenerative therapies due to their multipotency and ready availability, but their application can be complicated by patient-specific factors like age or illness. MSCs have been investigated for the treatment of many musculoskeletal disorders, including osteoarthritis and osteoporosis. Due to the prevalence of these diseases in older populations, researchers have studied how aging affects MSC properties and have found that proliferation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
199
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(207 citation statements)
references
References 65 publications
(74 reference statements)
6
199
0
2
Order By: Relevance
“…Although autologous stem cell transplantation holds some advantages, including safety of approach and reduction of virus or disease transmission; it also has disadvantages, namely the uncertainty of stem cell quality. Several studies have shown stem cell quality significantly decreases in older patients, and under certain conditions (Beane et al, 2014;Nakamura et al, 2016). Therefore, allogeneic stem cell therapy is regarded as a considered as suitable alternative to autologous transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although autologous stem cell transplantation holds some advantages, including safety of approach and reduction of virus or disease transmission; it also has disadvantages, namely the uncertainty of stem cell quality. Several studies have shown stem cell quality significantly decreases in older patients, and under certain conditions (Beane et al, 2014;Nakamura et al, 2016). Therefore, allogeneic stem cell therapy is regarded as a considered as suitable alternative to autologous transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…UCMSCs have also made great strides; unlike adipose tissue and BM, UC contains various compartments of stem cells, such as in cord-lining membrane, Wharton's jelly, cord vein, MODULATIST TM show strong immunomodulation capacity and blood. Studies have shown that MSCs can be successfully isolated from whole UC or from each compartment (Bieback and Netsch, 2016;Lim and Phan, 2014;Raoufil et al, 2015;Watson et al, 2015;Zhang et al, 2011). The isolated MSCs successfully differentiate into various functional cells, including adipocytes, osteoblasts, and chondroblasts, and also successfully transdifferentiate into hepatic-like cells, neuron-like cells, and cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…According to current literature the anatomical site of the adipose tissue does not affect the total number of viable cells that can be obtained from the subcutaneous fatty tissue [32,33]. Compared with mesenchymal stem cells from bone marrow biopsies, ADSC show also no statistically significant correlation between ADSC stem cell quality, proliferation capacity and the patient's age [34]. Additionally, ADSC implicate an equal differentiation potential into cells and tissues of mesenchymal origin [35].…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of ADSCs is relatively simple, with minimum donor site morbidity. More importantly, compared to other agedependent adult stem cells, such as bone marrow-derived mesenchymal stem cells (BMSCs), the quality and proliferation capacities of ADSCs do not decline with the age of the patient [9][10][11]. ADSCs are therefore a superior cell to other types of adult stem cells as a source for clinical approaches.…”
Section: Introductionmentioning
confidence: 99%